Corpo e duração – uma experimentação performativa - Lima, Elizabeth Maria Freire de Araújo; Inforsato, Erika Alvarez; Castro, Eliane Dias de (Rapsódia, 2020)
We resume the creative and conceptual processes proposed at the short-course Body and duration, held at the IV Seminar on Aesthetics and Art Criticism: reception policies, which took place in September 2019, at the School of Philosophy, Literature and Human Science of USP. The triggering and mobilizing axes of the body and duration connection are presented, linked to the movements and the persistence of living, in their relationship with culture, affections and ways of existence. The event articulated two distinct temporalities: a corporal one, with its mobilizations and aesthetic-clinical variations, interwoven with the conceptual work, generating critical openings. Clinical experience was considered, based on occupational therapy, which places the proposal on a territory that promotes philosophical thinking and concepts management while considering the life circumstances of the people treated on this field. Performativity was considered while highlighting that the constitution of something (of the body, subjectivity, gender) occurs through acts, gestures, experiences and language, – in dialogue with artistic experiments from the 60’s and continuing in contemporary performances and artistic practices that interweave aesthetic, social and political questions. These practices and reflections, linked to poststructuralist and contemporary philosophical formulations inserted in the clinical field, problematize the production of collective knowledge.